Stigma associated with people with HIV in Latin America: a systematic review - Macías, Jesús V.; Andrade, Natalia J.; Saltos, Gandy N.; Vélez, María J.; Soledispa, Danna S.; Párraga, María T.; Galarza, Judtih (Revista Gregoriana de Ciencias de la Salud, 2025)
One of the main consequences of having HIV is living with social stigma, where Latin American society expresses discrimination and ignorance. This article analyzes the current paradigm on the stigma associated with HIV-positive patients in Latin America. An exploratory systematic review was carried out, which used Scopus and SciELO as information sources of works published between 2013 and 2023. Inclusion criteria were applied: articles related to HIV and scientific publications in English and Spanish. The exclusion criteria were duplicate theses and articles. From the content analysis, four themes were identified: quality of life of people with HIV in Latin America, stigma towards people with HIV, paradigms in Latin American society regarding HIV, and strategies to eliminate stigma toward people with HIV. It was determined that the lack of education about sexuality and HIV contributes to the continuity of stigmas in Latin American society based on prejudices and erroneous beliefs.